The Effect of Learning Readiness on The Learning Outcomes of Economic Subjects in Class XI SMAN 1 Talibura - Merci, Apriliana Nona (EDUCTUM: Journal Research, 2022)
Learning readiness is a condition of students who are ready to take lessons in terms of giving responsis or answers in both physical and mental abilities. Based on a survey conducted at SMA Negeri 1 Talibura, many students were not ready to receive economics. This is seen by the lack of student’s attention when the teacher explains the material in front, so the that the material delivered by the teacher is not accepted by students and there are still many students who do not study the material in depth so they only depend on the material delivered by the teacher alone. In addition, students only have a reference book prepared by the school, students should also have to have othercompanion books so that they can add to their horizons. This research was conducted at SMA Negeri 1 Talibura with the aim to determine the effect of learning readiness on learning outcomes economic subjects in class XI SMA Negeri 1 Talibura. The population in this study was the whole of the research object, namely the number of all students of class XI Social Sciences. The sample used in this study was a random sampling technique. The method used in this study is quantitative descriptive. The hypothesis in this study is that there is a positive and significant influence on lerning outcomes in economic subjects in class XI SMA Negeri 1 Talibura. Data collection used are documentation techniques and questionnaire. Data analysis used in this study is a simple regression analysis. This is based on a simple regression analysis obtained by the results of tocunz of 4,042 greater than the trabel of 0,198 and based on the results of the analysis of the coefficient of determination obtained a score of 0,168 which means that the magnitude of the effect of leaerning readiness on learning outcomes is 16,8%.